2022
DOI: 10.3390/ijerph19031498
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and Depression among African American Adults: A Scoping Review of Current Research

Abstract: Depression in the United States (US) is increasing across all races and ethnicities and is attributed to multiple social determinants of health (SDOH). For members of historically marginalized races and ethnicities, depression is often underreported and undertreated, and can present as more severe. Limited research explores multiple SDOH and depression among African American adults in the US. Guided by Healthy People (HP) 2030, and using cross-disciplinary mental health terminology, we conducted a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 134 publications
0
12
0
1
Order By: Relevance
“…In addition, group therapy is a good setting for efficiently teaching adaptive coping skills that are helpful to improve patients’ mood, self‐efficacy, self‐care abilities, and quality of life. Of note, both before and during the COVID‐19 pandemic, people who identify as a member of a marginalized group (and especially with racial and ethnic minority groups) have experienced disparities in access to mental health and rehabilitative care, quality of the care delivered, and clinical outcomes achieved 118–120 . Every effort should be made to close gaps in these health disparities and ensure optimal care for this population.…”
Section: Treatment Options For Mental Health Symptoms In Persons With...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, group therapy is a good setting for efficiently teaching adaptive coping skills that are helpful to improve patients’ mood, self‐efficacy, self‐care abilities, and quality of life. Of note, both before and during the COVID‐19 pandemic, people who identify as a member of a marginalized group (and especially with racial and ethnic minority groups) have experienced disparities in access to mental health and rehabilitative care, quality of the care delivered, and clinical outcomes achieved 118–120 . Every effort should be made to close gaps in these health disparities and ensure optimal care for this population.…”
Section: Treatment Options For Mental Health Symptoms In Persons With...mentioning
confidence: 99%
“…Of note, both before and during the COVID-19 pandemic, people who identify as a member of a marginalized group (and especially with racial and ethnic minority groups) have experienced disparities in access to mental health and rehabilitative care, quality of the care delivered, and clinical outcomes achieved. [118][119][120] Every effort should be made to close gaps in these health disparities and ensure optimal care for this population. Public health initiatives should provide culturally responsive support to these minoritized groups.…”
Section: Non-pharmacologic Treatmentmentioning
confidence: 99%
“…The presence of physical or mental comorbidities together with multiple social factors can be equally prominent contributors to those suffering from MDD. In this sense, ethnic minorities, marital status (separated/divorced), poor education and healthcare access/quality, neighborhood, built environment, intimate partner violence, and lower socioeconomic resources are the most important social determinants related to the onset of MDD [ 7 , 12 , 13 ].…”
Section: Major Depressive Disorder and Diet: What Is The Relationship?mentioning
confidence: 99%
“…Racial status and culture may strongly influence dietary patterns and food preferences, consequently impacting overall health and disease susceptibility. Besides dietary behaviors, research has shown that social and environmental determinants of health, as opposed to genetic differences, are critical in propagating the burden of chronic disease disparities in African Americans [ 22 25 ]. Blacks are over-represented in lower-wage jobs and more likely to live in lower-income neighborhoods disproportionately higher in poverty compared to White neighborhoods [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%